Go! - Bravo, Becky; Vanessa Tamayo ([Place of publication not identifed] : [publisher not identified], 2013)
Slow and pale Jack only eats chips and sweets. He doesn't like healthy food at all. Then one day, he discovers potatoes.
Keywords: CHILDREN'S LITERATURE -- PHILIPPINES